Plasma neurofilament light and phosphorylated tau 181 as biomarkers of Alzheimer’s disease pathology and clinical disease progression - Clark, Christopher; Lewczuk, Piotr; Kornhuber, Johannes; Richiardi, Jonas; Maréchal, Bénédicte; Karikari, Thomas K.; Blennow, Kaj; Zetterberg, Henrik; Popp, Julius (Alzheimer's Research and Therapy, 2021)
Background: To assess the performance of plasma neurofilament light (NfL) and phosphorylated tau 181 (p-tau181) to inform about cerebral Alzheimer’s disease (AD) pathology and predict clinical progression in a memory clinic setting. Methods: Plasma NfL and p-tau181, along with established cerebrospinal fluid (CSF) biomarkers of AD pathology, were measured in participants with normal cognition (CN) and memory clinic patients with cognitive impairment (mild cognitive impairment and dementia, CI). Clinical and neuropsychological assessments were performed at inclusion and follow-up visits at 18 and 36 months. Multivariate analysis assessed associations of plasma NfL and p-tau181 levels with AD, single CSF biomarkers, hippocampal volume, and clinical measures of disease progression. Results: Plasma NfL levels were higher in CN participants with an AD CSF profile (defined by a CSF p-tau181/Aβ1–42 > 0.0779) as compared with CN non-AD, while p-tau181 plasma levels were higher in CI patients with AD. Plasma NfL levels correlated with CSF tau and p-tau181 in CN, and with CSF tau in CI patients. Plasma p-tau181 correlated with CSF p-tau181 in CN and with CSF tau, p-tau181, Aβ1–42, and Aβ1–42/Aβ1–40 in CI participants. Compared with a reference model, adding plasma p-tau181 improved the prediction of AD in CI patients while adding NfL did not. Adding p-tau181, but not NfL levels, to a reference model improved prediction of cognitive decline in CI participants. Conclusion: Plasma NfL indicates neurodegeneration while plasma p-tau181 levels can serve as a biomarker of cerebral AD pathology and cognitive decline. Their predictive performance depends on the presence of cognitive impairment.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Alzheimer’s; Biomarkers; Neurofilament light; p-tau181; Plasma